Effect of staining and bleaching on color stability and surface roughness of three resin composites: An in vitro study - Abha Telang; Indiresha H Narayana; K S Madhu; Dinesh Kalasaiah; Poornima Ramesh; Shruthi Nagaraja (Wolters Kluwer Medknow Publications, 2018)
Aim: This study evaluated the effect of staining and subsequent bleaching on the color stability and surface roughness of three resin composites. Materials and Methods: One hundred and eight customized plastic disks from a plastic mold with an outer diameter of 10 mm and thickness of 1.02 mm were fabricated. Samples were divided into three groups of 36 specimens each - Group I (Estelite® α - Supranano), Group II (Filtek™ Z250 XT - Nanohybrid), and Group III (Filtek™ P90-Silorane). Subsequently, baseline surface color and roughness values were tabulated using spectrophotometer and profilometer, respectively. The specimens were then subjected to staining with coffee and turmeric for a period of 3 h/day for 40 days and following this, bleaching of the samples was done using a bleaching agent carbamide peroxide gel 15% for 8 h/day for 14 consecutive days. Results: Estelite® α performed better by maintaining color stability with minimal roughness compared to Filtek™ P90 and Filtek™Z250 XT. Turmeric had a greater potential to stain composites compared to coffee in all the groups.